2015
DOI: 10.1111/jmp.12206
|View full text |Cite
|
Sign up to set email alerts
|

Renal evaluation with B‐mode and Doppler ultrasound in captive tufted capuchins (Sapajus apella)

Abstract: Both kidneys showed similar morphometric parameters by B-mode ultrasound, whereas RI by spectral Doppler decreased progressively from renal artery to interlobar and arcuate arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…We found no differences between the right and left kidneys for all biometric parameters, which is similar to previous studies in S. apella 29,30 and Macaca mulatta, 7 but contrasts with studies in other species. For instance, studies in the platyrrhine primates A. azarae infulatus 8 and in C. jacchus 25 reported that the left kidney had a greater height and length than the right kidney.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We found no differences between the right and left kidneys for all biometric parameters, which is similar to previous studies in S. apella 29,30 and Macaca mulatta, 7 but contrasts with studies in other species. For instance, studies in the platyrrhine primates A. azarae infulatus 8 and in C. jacchus 25 reported that the left kidney had a greater height and length than the right kidney.…”
Section: Discussionsupporting
confidence: 84%
“…The ultrasound appearance of the kidneys in both species was similar to that described previously in other Platyrrhines, including A. fusca , 28 S. apella , 29,30 A. azarae infulatus 10 and S. collinsi , 26 in which both kidneys had an elliptical shape, echogenicity and homogeneous cortical echotexture with preserved corticomedullary differentiation. One study in C. jacchus , reported a poor corticomedullary distinction in the kidneys, 25 which could have been due to the small size of these primates.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation